Environmental aspects of trenchless pipe rehabilitation methods. Issue 8 (14th September 2022) - Fuselli, F.; Huber, S.; Mambretti, S.
ABSTRACT: Trenchless methods for pipe rehabilitation have been increasing in popularity in recent years. Among the different advantages they have (e.g. less indirect costs) the paper deals with the environmental impact. In particular, the concept of carbon footprint is used to assess the environmental advantage in the use of CIPP and, among the different technologies presently available for this method, to indicate the more environmental friendly. The methods for calculation of carbon emissions are shown and then a simple analysis, for a theoretical case first, and then for a real case, are carried out. Critical considerations are finally presented.